Redes y eticidad como pensamiento estratégico de la comunicación organizacional frente a los legados de la cultura de la “gran madre” - Maciel González, Miguel Angel (Mediaciones Sociales, 2008)
This article aims at proposing and reflecting on the need to build a general communicative mediation model in general; and the development of life in organizations in particular, based on the social participation and collaboration constituted as a new perspective that allows not only to understand the complexity of the communicative phenomenon, but also to make habitable and sustainable our condition of existence in the social and institutional worlds. Thus, a model that helps to safeguard us as specie facing two cultural phenomena that have gained prominence when it comes to values and communication. One of them refers to the belief that every authority, just because it is, becomes in itself sacred, therefore, untouchable and unsuitable for criticism, based on the legacy given to us by the great mother. And two, how this phenomenon of the sacred is taken by capitalism to develop new ways of symbolic communication which elaborate a communications discourse mainly commercial (this can be observed in the languages of the enter-prises) and the reduction of the communicative feat.